2020
DOI: 10.5223/pghn.2020.23.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Gastrointestinal Symptoms associated with Antibiotic Treatment in Children: A Population Study

Abstract: Purpose: Gastrointestinal symptoms are often related to antibiotic treatment. Their incidence, risk and protective conditions in children are not well defined and represent the aims of this study. Methods: We prospectively enrolled inpatient children submitted to antibiotic treatment. Indication, type, dose and duration of treatment, probiotic supplementation and gastrointestinal symptoms were recorded at recruitment, after two and four weeks. Antibiotic-associated diarrhea (AAD) was defined as the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
(37 reference statements)
0
14
0
1
Order By: Relevance
“…It is sometimes difficult to distinguish the gastrointestinal symptoms of pediatric COVID-19 from those caused by another viral illness, side effects of drugs, and digestive tract symptoms such as nausea and diarrhea caused by the disturbance of gastrointestinal flora by the fever itself. Some studies 49 have found that 20.4% children use antibiotics that cause diarrhea, and the diarrhea is more severe in younger patients with lower respiratory tract infections treated with intravenous antibiotics. Moreover, we discovered that the total incidence of gastrointestinal symptoms in children with COVID-19 was 17.7%; unfortunately, not all the studies described a control group when investigating the incidence of gastrointestinal symptoms in an antibiotic treatment group and non-antibiotic treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…It is sometimes difficult to distinguish the gastrointestinal symptoms of pediatric COVID-19 from those caused by another viral illness, side effects of drugs, and digestive tract symptoms such as nausea and diarrhea caused by the disturbance of gastrointestinal flora by the fever itself. Some studies 49 have found that 20.4% children use antibiotics that cause diarrhea, and the diarrhea is more severe in younger patients with lower respiratory tract infections treated with intravenous antibiotics. Moreover, we discovered that the total incidence of gastrointestinal symptoms in children with COVID-19 was 17.7%; unfortunately, not all the studies described a control group when investigating the incidence of gastrointestinal symptoms in an antibiotic treatment group and non-antibiotic treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…It is sometimes di cult to distinguish the gastrointestinal symptoms of pediatric COVID-19 from those caused by another viral illness, side effects of drugs, and digestive tract symptoms such as nausea and diarrhea caused by the disturbance of gastrointestinal ora by the fever itself. Some studies 49 have found that 20.4% children use antibiotics that cause diarrhea, and the diarrhea is more severe in younger patients with lower respiratory tract infections treated with intravenous antibiotics. Moreover, we discovered that the total incidence of gastrointestinal symptoms in children with COVID-19 was 17.7%; unfortunately, not all the studies described a control group when investigating the incidence of gastrointestinal symptoms in an antibiotic treatment group and non-antibiotic treatment group.…”
Section: Incidence Of Gastrointestinal Symptomsmentioning
confidence: 99%
“…immunoassay [37]. In one study, testing for rota-and noroviruses was performed, but a specific method was not reported [57].…”
Section: Plos Onementioning
confidence: 99%
“…Among other characteristics of the diarrhea, its duration was reported in only 9 out of 33 studies, which corresponds to 27% of the studies with diarrhea as an outcome. In 6 of these studies, the duration was not defined [8,28,29,31,53,57], whereas in each of the 3 remaining studies its definition varied [30,33,47]. Diarrhea severity was reported as an outcome in only 4 of the studies (12%), and it was defined differently in every one of them, usually on the basis of discharge frequency and stool consistency [7,28,30,34].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation